Autophagy metabolically suppresses CD8+ T cell antitumor immunity. Issue 9 (2nd September 2019) - Carleton, Gillian; Lum, Julian J.
ABSTRACT: Macroautophagy/autophagy is a critical regulator of adaptive T cell immunity and homeostasis. However, the role of T cell autophagy in regulating antitumor immune responses is less clear. In a recent study, we showed that deletion of the essential autophagy genes Atg5, Atg14, or Atg16l1 in host tissues dramatically impairs growth of autophagy-competent syngeneic tumors. We further demonstrated that CD8 + T cells lacking Atg5 acquire an effector memory phenotype and produce more IFNG/IFN-γ (interferon gamma) and TNF/TNF-α (tumor necrosis factor). These phenotypic changes are accompanied by enhanced glucose metabolism that results in alterations in histone methylation, and upregulation of glycolytic and immune response genes. In accordance with this, we observed control of tumor growth in autophagy-competent mice after adoptive transfer with a sub-therapeutic dose of atg5 -/- T cells. Collectively, we discovered a unique, cell-autonomous role for T cell autophagy in the metabolic control of antitumor immunity.